Treatment with (chemo)-radiation in old patients (≥76 years of age) with newly diagnosed non-metastatic squamous cell cancer of the head and neck region: real-world data from a tertiary referral center - Winkler, Leah-Sophie; Haderlein, Marlen; Semrau, Sabine; Putz, Florian; Höfler, Daniel; Müller, Sarina K.; Iro, Heinrich; Kesting, Marco; Fietkau, Rainer; Schubert, Philipp (Frontiers in Oncology, 2024)
Treatment of patients with squamous cell carcinoma of the head and neck region (HNSCC) is in focus of a multitude of studies. In those, one patient group, aging 76 and more is mostly underrepresented despite requiring thorough and well-reasoned treatment decisions to offer curative treatment. This study investigates real-world data on curative treatment of old (76 years) patients with newly diagnosed HNSCC. Between January 2010 and December 2021, we identified 71 patients, older then76 years with newly diagnosed HNSCC and cM0 at the department of Radiation Oncology of the university hospital of Erlangen-Nuremberg. Using electronic medical records, we analyzed treatment patterns and outcomes in terms of overall survival (OS), progression survival (PFS) and locoregional control rate (LRC). Additionally, univariate risk analysis and cox regression was performed in order to identify predictive factors associated with above mentioned treatment outcomes. Median follow-up was 18 months. OS was 83%, 79% and 72% after 1, 2 and 3 years. PFS was 69%, 54% and 46% after 1, 2 and 3 years. 34 (48%) patients were treated by standard therapy according to current guidelines. Reasons for deviation from standard therapy before or during treatment were: Unfitness for cisplatin-based chemotherapy (n=37), reduction of chemotherapy(n=3) and dose reduction/interruption of radiotherapy(n=8). carboplatin-based systemic therapy showed improved PFS compared to cisplatin or cetuximab (60 vs 28 vs 15 mths, p=0.037) but without impact on OS (83 vs 52 vs 38 mths, p=0.807). Oropharyngeal tumor localization (p=0.026) and combined treatment (surgery and postoperative treatment) (p=0.008) were significant predictors for a better OS. In multivariate analysis oropharyngeal tumor localization (p=0.011) and combined treatment (p=0.041) showed significantly increased PFS. After 1, 2 and 3 years, the cumulative incidence of locoregional recurrences(LRR) was 13%, 24% and 27% and was significantly decreased in patients with oropharyngeal tumor localization (p=0.037). Adherence to treatment protocols for radiotherapy alone in old patients with HNSCC is good, whereas the application of concurrent chemotherapy often deviates from guidelines in terms of de-escalation. An important risk factor for decreased OS, PFS and a higher rate of LRR appears to be non-oropharnygeal tumor location in old patients.